2003
DOI: 10.1097/01.jom.0000083034.56116.0f
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Farming, Occupational Solvent Exposures, and the Risk of Oral Cancer in Puerto Rico

Abstract: The work history information from a population-based case-control study conducted in Puerto Rico was analyzed using a job exposure matrix to investigate the relationship between occupational exposures and cancers of the oral cavity or pharynx. After adjustment for age, alcohol, smoking, and residence in a logistic model, the risk for cancer of the oral cavity, but not the pharynx, was significantly elevated among farm workers in the sugarcane industry (OR = 4.4, 95% CI = 1.4-13.6). An exposure-response trend w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
1
24
0
1
Order By: Relevance
“…In order to evaluate farmers' exposure to organic solvents during their farming activities and to assess the risk of potential health outcomes, we conducted this pilot study. Consistent with other published studies [Coble et al, 2002[Coble et al, , 2003Wu et al, 2003;Amshoff and Reed, 2005], we found that farm machinery maintenance and repair was a primary task performed by Kentucky farmers. Many farmers used solvent-containing products as primary agents for the maintenance and repair of their farm machinery which allowed them to have direct contact with organic solvents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In order to evaluate farmers' exposure to organic solvents during their farming activities and to assess the risk of potential health outcomes, we conducted this pilot study. Consistent with other published studies [Coble et al, 2002[Coble et al, , 2003Wu et al, 2003;Amshoff and Reed, 2005], we found that farm machinery maintenance and repair was a primary task performed by Kentucky farmers. Many farmers used solvent-containing products as primary agents for the maintenance and repair of their farm machinery which allowed them to have direct contact with organic solvents.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies reported that solvent exposure in farmers can occur when performing a variety of different farm tasks [Blair and Zahm, 1995;Coble et al, 2002Coble et al, , 2003Hoppin et al, 2004;Perry and May, 2005;van Balen et al, 2006], we focused our quantitative dermal exposure assessment on farm machinery maintenance and repair tasks because these are the main tasks performed by farmers in Kentucky. The results revealed that significant amounts of solvents were detected on both hands when farmers performed maintenance and repair tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses were restricted to dichotomic indices of exposure (ever/never), and results were reported as a meta-RR. In three case-control studies (Berrino et al 2003;Coble et al 2003;Gustavsson et al 1998), the ''ever exposed'' category was not available and impossible to infer from the reported data. For these three studies, we used the extreme categories (low and high, possible, and probable) of the exposure score and combined each in turn with the ''ever'' category from the other studies.…”
Section: Methodsmentioning
confidence: 99%
“…In a Puerto Rican case-control study on oral and pharyngeal cancers (Coble et al 2003), the authors underlined a significant dose-response relationship with cumulative exposure to solvents, with ORs reaching 1.6 and 3.2 for the medium and high exposure categories, respectively. In a Finnish record linkage study (Tarvainen et al 2008), slight increases in the number of cancer cases of OC, HP, OP were observed when exposure to organic solvents was considered.…”
Section: Solventsmentioning
confidence: 99%